Purely Electrical Controllable Complete Spin Logic in a Single Magnetic Heterojunction. (26th July 2021) - Zhao, Xiaonan; Dong, Yanan; Chen, Weibin; Xie, Xuejie; Bai, Lihui; Chen, Yanxue; Kang, Shishou; Yan, Shishen; Tian, Yufeng
Abstract: Fully electrical manipulation of magnetism, preferably through spin current, is highly desired to achieve energy‐efficient, nonvolatile, and programmable spin logic devices. It is demonstrated in this study that in a single Pt/IrMn/Co/Ru/CoPt heterojunction, all 16 Boolean logic functions can be realized in a purely electrical way, relying on electrical manipulation of magnetic‐field‐free spin‐orbit torque (SOT) switching. By applying current pulses along with two orthogonal directions, the exchange bias between IrMn and Co, and the SOT switching polarity (clockwise or counterclockwise) of perpendicularly magnetized CoPt, can be reversibly controlled, enabling complete spin logic within a single nonvolatile memory. This study makes a significant step towards practical electrical programmable spin logic devices. Abstract : Purely electrical controllable complete spin logic is demonstrated in a single Pt/IrMn/Co/Ru/CoPt heterojunction. By applying current pulses along two orthogonal directions, all 16 Boolean logic functions can be realized in a purely electrical way, relying on the electrical manipulation of magnetic‐field‐free spin‐orbit torque switching. This study makes a significant step towards practical electrical programmable spin logic devices.